A comparative study of the prophets of African indigenous Churches and Akan Traditional Priests: A critical examination of their training. - Owusu, Joseph Atuahene (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of Master of Philosophy degree in Religious Studies.